Awareness regarding weaning and its associated factors among mothers in rural Sindh - Ahsan Ali Dahani; Syed Imtiaz Ahmed Jafry; Syed Muhammad Zulfiqar Hyder Naqvi; Munir Ahmed Shaikh; Muhammad Zafar Iqbal Hydrie; Muhammad Zahid Shah (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2020)
Objective: To determine the awareness regarding weaning and its associated factors among mothers in Kashmore, rural Sindh.